The Influence of Locus of Control, Self-Efficacy, and Adversity Quotient on Business Performance - Titien Agustina; Nurhikmah Nurhikmah; Muhammad Rudiansyah (Jurnal Economia, 2022)
AbstractThis study aims to measure the Locus of Control, Self-Efficacy, and Adversity Quotient of owners or managers on the performance of Badan Usaha Milik Desa (BUMDes), which have a similar condition as Micro, Small and Medium Enterprises (SME). The number of research samples is 53 respondents. Data were analyzed using multiple regression. The results showed that Locus of Control (2,080), Self-Efficacy (2,085), Adversity Quotient (5,162) had a positive and partially significant effect on Business Performance. Locus of control, Self-Efficacy, and Adversity Quotient have a positive and significant impact simultaneously on Business Performance (183,523). Adversity quotient has the most dominant effect on Business Performance compared to Locus of Control and Self-Efficacy. These results indicate that high adversity intelligence encourages business performance by utilizing limited capital, capabilities, labor, networks, markets, opportunity.Keywords: locus of control, self-efficacy, adversity quotient, business performance, BUMDes.Pengaruh Locus of Control, Self-Efficacy, dan Adversity Quotient Terhadap Kinerja UsahaAbstrakPenelitian ini mengukur Locus of Control, Self-Efficacy, dan Adversity Quotient pemilik atau manajer terhadap kinerja Badan Usaha Milik Desa (BUMDes) yang hampir sama kondisinya dengan Usaha Mikro, Kecil, dan Menengah (UMKM). Jumlah sampel penelitian 53 orang. Data dianalisis menggunakan regresi berganda. Hasil penelitian menunjukkan Locus of Control 2,080, Self-Efficacy 2,085, Adversity Quotient 5,162 berpengaruh positif dan signifikan secara parsial terhadap Kinerja Usaha. Locus of control, Self-Efficacy, dan Adversity Quotient berpengaruh positif dan signifikan secara simultan terhadap Kinerja Usaha 183,523. Adversity quotient berpengaruh paling dominan terhadap Kinerja Usaha dibandingkan Locus of Control dan Self-Efficac. Artinya kecerdasan adversitas yang tinggi mampu mendorong peningkatan kinerja usaha yang dijalankan dengan memanfaatkan keterbatasan modal, kemampuan, tenaga kerja, jaringan, pasar, dsb tetapi sebaliknya menjadi daya dorong untuk makin cerdas dalam melihat peluang dan meraih kesempatan-kesempatan.Kata kunci: locus of control, self-efficacy, adversity quotient, kinerja Usaha, BUMDes